The efficiency of the microbial carbon pump as seen from the relationship between apparent oxygen utilization and fluorescent dissolved organic matter. (January 2023) - Xiao, Xilin; Yamashita, Youhei; Gonsior, Michael; Jiao, Nianzhi
Highlights: The slope of AOU–FDOMH relationship is the proxy of RDOM production efficiency. A global comparable oceanic AOU–FDOMH relationship dataset is obtained. The general tendencies of the slope of AOU–FDOMH relationship were discussed. Factors that may affect the AOU–FDOMH relationship are summarized. Applicable at a global scale in future studies are proposed. Abstract: The mechanism behind the source/production of refractory dissolved organic matter (RDOM) in the ocean remains an enigma, but the biological origin of RDOM has now been recognized and conceptualized as the microbial carbon pump (MCP). Consequently, the development of a proxy for the efficiency of the MCP production of RDOM is desirable. It has widely been observed that marine humic-like fluorescent dissolved organic matter (FDOMH ) is linearly correlated with apparent oxygen utilization (AOU), and hence it is promising for exploring this relationship. Here, we discuss whether the slope of the AOU–FDOMH correlation can be an indicator for evaluating the MCP efficiency in the dark ocean. We gathered all the peer-reviewed literature on AOU–FDOMH relationships and summarized the general results and factors that may affect this relationship. Finally, we propose to make the AOU–FDOMH relationship comparable and applicable at a global scale in future studies to better constrain sources and sinks of FDOMH and its link to heterotrophic microbial respiration, namely, the FDOM-based MCP efficiency.